The Effect Of Funds Management, Promotion and Service Quality on Customer Loyalty at Bank BJB Bekasi - Arviana Wulandari (International Journal of Education, Information Technology, and Others, 2021)
Purpose: to find out: (1) whether management has a positive effect on customer loyalty, (2) whether promotion has a positive effect on customer loyalty, (3) whether service quality has a positive effect on customer loyalty, (4) whether fund management, promotion, service quality together -the same has a positive effect on customer loyalty. Design/methodology/approach: descriptive and verification method. Findings: The results of this analysis indicate that the effect of price on customer loyalty has a positive and significant effect. The effect of promotion on customer loyalty has a positive and significant effect. The effect of service quality on customer loyalty has a positive and significant effect. The effect of price, promotion, and service quality on customer loyalty has a positive and significant effect. Research limitations/implications: There are four variables considered in this paper: fund management, promotion, quality of service, and customer loyalty; Intervening variables are not considered and the sample for this study is 100 using a non-probability sampling method. Originality/value: This Paper is Original. Paper type: Research Paper